WHAT ARE THE FEMALE CHALLENGES IN HOSPITALITY INDUSTRY IN UZBEKISTAN: WOMAN WORKERS’ PERSPECTIVE - Aktamova, Zarniso (Журнал иностранных языков и лингвистики, 2023)
The present paper aims to examine the major challenges and issues that female workers of hospitality industry face during their carrier ladder and work time in Uzbekistan. A number of studies has been done about this problem, however all of them are from the perspective of general managers or they differentiate the performance of men and women by their ability, communication skills and dedication. The primary purpose of this undertaken study is to find out the opinion of female staff towards problems related to their job. To analyze the equity of female workers in lodging industry demographic data was gathered and a sample was selected from different position owners of the industry in order to conduct a questionnaire. Twenty women were interviewed face-to-face and the records’ transcript were made to evaluate the problems.